2020
DOI: 10.1371/journal.pone.0240307
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and health effects in juvenile haddock (Melanogrammus aeglefinus) exposed to PAHs associated with oil-polluted sediment or produced water

Abstract: The research objective was to study the presence of DNA damages in haddock exposed to petrogenic or pyrogenic polyaromatic hydrocarbons (PAHs) from different sources: 1) extracts of oil produced water (PW), dominated by 2-ring PAHs; 2) distillation fractions of crude oil (representing oil-based drilling mud), dominated by 3-ring PAHs; 3) heavy pyrogenic PAHs, mixture of 4/5/6-ring PAHs. The biological effect of the different PAH sources was studied by feeding juvenile haddock with low doses of PAHs (0.3-0.7 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 94 publications
1
16
0
1
Order By: Relevance
“…Hence, three modes of action have previously been described in teleost species, including Ahr-independent, Ahr-dependent, and Cyp1a metabolism-dependent. ,,, While adverse effects on Atlantic cod have been demonstrated after crude oil and produced water exposure, limited information exists for this species regarding the toxicity mediated by the individual chemical constituents, such as unsubstituted and substituted PACs. However, it was shown in juvenile Atlantic haddock (Melanogrammus aeglefinus), which is another Gadiform species, that among 12 injected unsubstituted heavy PAHs, including BAP, benz­[ a ]­anthracene, dibenz­[ a , h ,]­anthracene, and CHR, produced high levels of DNA adducts in the liver . Furthermore, it has also been shown that intramuscular injections of NAP, CHR, and their corresponding dihydrodiol metabolites R , R -1,2-DHN and (1 R ,2 R )-1,2-dihydrochrysene-1,2-diol result in the formation of PAH-protein adducts in the Atlantic cod plasma proteome and possibly a triggered immune response .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, three modes of action have previously been described in teleost species, including Ahr-independent, Ahr-dependent, and Cyp1a metabolism-dependent. ,,, While adverse effects on Atlantic cod have been demonstrated after crude oil and produced water exposure, limited information exists for this species regarding the toxicity mediated by the individual chemical constituents, such as unsubstituted and substituted PACs. However, it was shown in juvenile Atlantic haddock (Melanogrammus aeglefinus), which is another Gadiform species, that among 12 injected unsubstituted heavy PAHs, including BAP, benz­[ a ]­anthracene, dibenz­[ a , h ,]­anthracene, and CHR, produced high levels of DNA adducts in the liver . Furthermore, it has also been shown that intramuscular injections of NAP, CHR, and their corresponding dihydrodiol metabolites R , R -1,2-DHN and (1 R ,2 R )-1,2-dihydrochrysene-1,2-diol result in the formation of PAH-protein adducts in the Atlantic cod plasma proteome and possibly a triggered immune response .…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that vertebral bone mineralization could be used as an early stress indicator of PAH pollution in sea bass. Vertebral malformation was also observed in juvenile haddock after a 2-month dietary exposure to produced water, oil, and heavy PAHs (Meier et al, 2020).…”
Section: Bone Developmentmentioning
confidence: 90%
“…Furthermore, this adduct was also identified as a major DNA adduct in mouse [ 52 , 53 ] or in human liver cells [ 54 ]. The potential of BaP to generate DNA adducts was also observed in fish [ 55 ]. However, the level of DNA adducts likely differ between species as BaP metabolism differs significantly between species [ 56 ].…”
Section: Discussionmentioning
confidence: 99%